A Seed-Borne Bacterium of Rice, Pantoea dispersa BB1, Protects Rice from the Seedling Rot Caused by the Bacterial Pathogen Burkholderia glumae - Yusuke Kouzai; Chiharu Akimoto-Tomiyama (Life, 2022)
Seedling rot, caused by the bacterial pathogen Burkholderia glumae, is a major disease of rice. It originates from pathogen-contaminated seeds and is thus mainly controlled by pesticide treatments of seeds. We previously demonstrated that the seed-borne bacteria of rice may be a useful and sustainable alternative to pesticides to manage seedling rot, but they are limited in terms of variety. Here, we report that another seed-borne bacterium, Pantoea dispersa BB1, protects rice from B. glumae. We screened 72 bacterial isolates from rice seeds of three genetically different cultivars inoculated or non-inoculated with B. glumae. 16S rRNA gene sequencing revealed that pathogen inoculation affected the composition of culturable seed-borne bacterial communities and increased the presence of Pantoea and Paenibacillus species. Among three Pantoea and Paenibacillus isolates that exhibit tolerance to toxoflavin, a virulence factor of B. glumae, P. dispersa BB1 significantly mitigated the symptoms of rice seedling rot. The culture filtrate of BB1 inhibited the growth of B. glumae in vitro, suggesting that this isolate secretes antibacterial compounds. Seed treatment with BB1 suppressed pathogen propagation in plants, although seed treatment with the culture filtrate did not. Because BB1 did not show pathogenicity in rice, our findings demonstrate that BB1 is a promising biocontrol agent against seedling rot.